Application of variational methods in chemical thermodynamics: a study of the stability of chemical systems - Reis, Martina Costa; Bassi, Adalberto Bono Maurizio Sacchi (Journal of mathematical chemistry, 2015)
The stability of chemical systems is discussed by using elementary concepts of control theory, and Lyapunov stability theory. From these concepts, a mathematically clear definition of irreversible thermodynamic processes and equilibrium states is established. Furthermore, it is shown that the extremum principles of classical thermodynamics can be obtained as natural consequences of the Lyapunov stability theory application in usual physicochemical systems. It is also demonstrated that for the case of chemical systems subject to more general physical conditions, it is possible to find a scalar function dependent of macroscopic parameters that describes the evolution of the system toward the equilibrium state. The aim of this work is to show that by using variational methods one can discuss the stability of many chemical systems.